2019
DOI: 10.1111/cjag.12208
|View full text |Cite
|
Sign up to set email alerts
|

An empirical assessment of food security on First Nations in Canada

Abstract: Using data generated from surveys conducted on First Nations throughout Canada, we use regression analysis to examine factors influencing food insecurity. To our knowledge, this is the first time a regression‐based analysis has been conducted to examine food insecurity on First Nations in Canada. As expected, income is inversely related to the likelihood that one reports their household as experiencing food insecurity. In addition, individuals in extremely remote areas are more likely to report their household… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…Given that the rate of food worry among those reporting financial worry was 33.5%, compared with 7.6% among those who did not report financial worry, our findings suggest that food worry was more prevalent among, although not necessarily limited to, households experiencing COVID-19-related income shocks and other financial concerns. This is a finding that aligns with previous household food security literature (Deaton et al, 2019;Tarasuk & Mitchell, 2020) as well as Canadian and US COVID-19 studies (Ahn & Norwood, 2020;Polsky & Gilmour, 2020). Niles et al (2020) reported that during the pandemic, food-insecure households in the USA were more likely to include an individual who had been furloughed, seen a reduction in hours, or lost their job since the start of the pandemic compared with food-secure households.…”
Section: Discussionsupporting
confidence: 89%
“…Given that the rate of food worry among those reporting financial worry was 33.5%, compared with 7.6% among those who did not report financial worry, our findings suggest that food worry was more prevalent among, although not necessarily limited to, households experiencing COVID-19-related income shocks and other financial concerns. This is a finding that aligns with previous household food security literature (Deaton et al, 2019;Tarasuk & Mitchell, 2020) as well as Canadian and US COVID-19 studies (Ahn & Norwood, 2020;Polsky & Gilmour, 2020). Niles et al (2020) reported that during the pandemic, food-insecure households in the USA were more likely to include an individual who had been furloughed, seen a reduction in hours, or lost their job since the start of the pandemic compared with food-secure households.…”
Section: Discussionsupporting
confidence: 89%
“…Our study contributes to a well-developed literature that emphasizes the strong association between higher incomes and a lower likelihood of food insecurity holding other factors constant (e.g. Che and Chen, 2001;Deaton, Scholz and Lipka, 2019;Tarasuk, Fafard St-Germain and Mitchell, 2019;Tarasuk and Vogt, 2009). Our emphasis on the variation in the severity of food insecurity amongst households categorized as food insecure is well articulated in government publications (Health Canada, 2020a) and previous research (e.g.…”
Section: Introductionmentioning
confidence: 52%
“…Previous research has established an important association between income and the risk of food insecurity: e.g., a $1000 increase in income reduces the odds of severe food insecurity by 5% (Tarasuk, Fafard St-Germain and Mitchell, 2019). In the context of Canadian First Nations, Deaton, Scholz and Lipka (2019) find that individuals in the lowest income category -$1-$9999are approximately 13 times as likely to be food insecure as individuals with an income of $90,000 or more. This general finding with respect to income and food insecurity is well established in other studies as well (e.g.…”
Section: Argument 2: Income and Food Price Considerations Are Paramountmentioning
confidence: 93%
See 1 more Smart Citation
“…Finally, CCHS 2015-Nutrition omitted people living in the territories and in First Nations communities. While these represent relatively small fractions of the total population, they are at particularly high risk of food insecurity (1,46,81) . Research is needed to understand how household food insecurity relates to diet quality and other measures of nutritional compromise in these particularly vulnerable groups.…”
Section: Discussionmentioning
confidence: 99%